The writers : a history of American screenwriters and their Guild - Banks, Miranda J., 1972- (Rutgers University Press, 2015)
The Writers is the only comprehensive qualitative analysis of the history of writers and writing in the film, television, and streaming media industries in America. Featuring in-depth interviews with over fifty writers--including Mel Brooks, Norman Lear, Carl Reiner, and Frank Pierson--The Writers delivers a compelling, behind-the-scenes look at the role and rights of writers in Hollywood and New York over the past century. Granted unprecedented access to the archives of the Writers Guild Foundation, Miranda J. Banks also mines over 100 never-before-published oral histories with legends such as Nora Ephron and Ring Lardner Jr., whose insight and humor provide a window onto the enduring priorities, policies, and practices of the Writers Guild. With an ear for the language of storytellers, Banks deftly analyzes watershed moments in the industry: the advent of sound, the Second World War, the blacklist, the ascension of television, the American New Wave, the rise and fall of VHS and DVD, and the boom of streaming media. The Writers spans historical and contemporary moments, drawing upon American cultural history, film and television scholarship, and the passionate politics of labor and management. --